Prokrastinasi Akademik Mahasiswa dalam Penyelesaian Skripsi di Prodi Pendidikan IPS Universitas Negeri Jakarta Angkatan 2017 – 2018 - Rahman, Aditya (Edukasi IPS, 2023)
This study aims to: (1) Describe academic procrastination in completing thesis for Social Sciences Education Study Program students, Jakarta State University class of 2017 – 2018, (2) Describe the factors that cause academic procrastination in completing thesis for Social Science Education Study Program students, Jakarta State University class of 2017 – 2018. This research was conducted in Building K, Social Sciences Education Study Program, Faculty of Social Sciences, Jakarta State University. The research method used is qualitative. Data collection techniques through observation, questionnaires, interviews, documentation, and literature studies. The subjects in this study were 10 respondents. The results of this study indicate that: (1) Student academic procrastination behaviour in the completion of thesis can be seen from several aspects such as perceived time, intention-action gap, emotional distress, and perceived ability. In this study, most students delay in the form of dysfunctional procrastination. (2) Internal factors that encourage students to carry out academic procrastination in completing their thesis are physical conditions and psychological conditions which consist of; intrinsic motivation, self-regulation, self-efficacy, and self-awareness. Then the external factors that encourage students to carry out academic procrastination in completing thesis are parents upbringing, environmental conditions, work, friends, and organization.   Abstrak Penelitian ini bertujuan: (1) Mendeskripsikan prokrastinasi akademik dalam penyelesaian skripsi pada mahasiswa Prodi Pendidikan IPS Universitas Negeri Jakarta angkatan 2017 – 2018, (2) Mendeskripsikan faktor penyebab prokrastinasi akademik dalam penyelesaian skripsi pada mahasiswa Prodi Pendidikan IPS Universitas Negeri Jakarta angkatan 2017 – 2018. Penelitian ini dilakukan di Gedung K, Prodi Pendidikan IPS Fakultas Ilmu Sosial Universitas Negeri Jakarta. Metode penelitian yang digunakan adalah kualitatif. Teknik pengumpulan data melalui observasi, kuesioner, wawancara, dokumentasi, dan studi kepustakaan. Subjek dalam penelitian ini terdapat 10 orang responden. Hasil penelitian ini menunjukan bahwa: (1) Perilaku prokrastinasi akademik mahasiswa dalam penyelesaian skripsi dapat terlihat dari beberapa aspek seperti perceived time, intention-action gap, emotional distress, dan perceived ability. Dalam penelitian ini, mayoritas mahasiswa melakukan penundaan dalam bentuk dysfunctional procrastination. (2) Faktor internal yang mendorong mahasiswa melakukan prokrastinasi akademik dalam penyelesaian skripsi adalah kondisi fisik dan kondisi psikologis yang terdiri dari; motivasi intrinsik, regulasi diri, efikasi diri, dan kesadaran diri. Kemudian faktor eksternal yang mendorong mahasiswa melakukan prokrastinasi akademik dalam penyelesaian skripsi adalah pola asuh orang tua, kondisi lingkungan, pekerjaan, teman, dan organisasi.